THE VENTURE CAPITAL AND PRIVATE EQUITY INDUSTRY IN CHINA, AND IMPLICATIONS OF THE CONTRIES' LEGAL SYSTEM ON THE INDUSTRY DEVELOPMENT - Huang, Peng (2007)
In the 1980s, the Chinese government realized the importance of the venture capital and private equity to the development of the economy, the venture capital industry has experienced dramatic growth ever since. Although, the Chinese venture capital industry is the second largest in the world, only after the United States, however, the current research studies on the Chinese venture capital industry are limited. In this study, the conceptual frameworks presented by Wright et al., and the life cycle model of the venture capital investment will be employed to explore the venture capital industry in China, The influence of the Chinese legal system over the development of the venture capital industry will also be discussed. The research study was done through a qualitative research methods, by employing interview and questionnaires methods, this paper finds that in the financial market where the legal frameworks are relatively less developed, the role of the legal and regulation has played far more important role than the developed market for the investment of the venture capitals. In China, the venture capital industry heavily depends on the government's policies and regulations, which both facilitates and blocks its development.